The main directions of efficiency optimization of transport and logistics system of suppliers of spare parts for agricultural machinery - V. V. Leushkina; O. V. Kondratieva; E. A. Pogrebtsova (Омский научный вестник: Серия "Общество. История. Современность", 2022)
Currently, the process of trucking is facing a number of problems and factors both internal and external. In order to increase the competitiveness of road carriers, it is necessary to improve logistics management methods. The theoretical and methodological basis of the research article is a logistics approach, expressed in a systematic approach to the study of the processes of organizing the production of a transport and logistics system in an enterprise engaged in the supply of spare parts for agricultural producers.